Antidiabetic potential of dietary polyphenols: A mechanistic review. (July 2021) - de Paulo Farias, David; de Araújo, Fábio Fernandes; Neri-Numa, Iramaia Angélica; Pastore, Glaucia Maria
Graphical abstract: Highlights: In this study, the antidiabetic effects of phenolic compounds were addressed. Dietary phenolic compounds have hypoglycemic effects. Phenolics reduce protein glycation and incretin hormones degradation. They can reduce inflammation, insulin resistance and preserve β-beta cell function. Their intake can modulate the gut microbiota and improve glucose metabolism. Abstract: Diabetes is a metabolic disorder that has caused enormous harm to the public health worldwide. In this study, we evaluated the potential of phenolic compounds on diabetes management, addressing their mechanisms of action, in addition to discussing the digestion, absorption, metabolism, bioavailability, and toxic effects of these compounds. The intake of phenolic compounds can play a fundamental role on diabetes management, since they can reduce blood glucose levels, oxidative stress, protein glycation, inhibit the activity of dipeptidyl peptidase - IV and other key enzymes related to carbohydrate metabolism, activate various biochemical pathways to improve pancreatic β-cell functions, increase insulin secretion, and improve insulin resistance. In this way, they can be considered a potential strategy in the development of pharmaceutical approaches that aim to reduce complications resulting from the progression of this metabolic pathology.